Prevention Behavior of COVID -19 Transmission in Productive Age - Ahmad Taufik; Solahuddin Harahap; Kaaf Wajiah Siregar; Yustika Anggraini Hasibuan; Nur Fadilah Hasibuan; Yuni Harmila Siregar; Zahrani Nabilah; Faiza Adinda (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
The coronavirus attacks the human respiratory tract. A person can get infected by a Covid-19 patient. The disease can spread through small droplets from the nose or mouth when coughing or sneezing. Transmission of the COVID-19 virus has two main ways, namely through respiratory droplets and contact. Respiratory droplets are produced when a person coughs or sneezes. Everyone in close contact (within a 1 m radius) with a person showing symptoms of respiratory distress (coughing, sneezing) is at risk of being exposed to respiratory droplets that may cause infection. Droplets can also fall onto surfaces where the virus remains active. A total of 93% of Medan city residents have implemented mask-wearing behavior. Seventeen respondents (56.7%) use a hand sanitizer constantly, 15 respondents (29.4%) use a hand sanitizer sometimes, and 28 respondents (54.9%) never use a hand sanitizer. According to the data shown in table 4 above, seven respondents (90%) always use physical separation, compared to one respondent (10%) who never does so. During the COVID-19 pandemic, we aim to continue to increase our body's immune system and maintain personal hygiene to avoid various diseases and the Covid-19 virus. We also hope for constructive criticism and suggestions from our friends so that the article we have created meets expectations and is useful for all of us